Advances in Theranostic Nanomedicine: Integrating Diagnosis and Therapy for Precision Cancer Treatment - Kumar, Ritu Raj; Antal, Sonakshi (Current Stem Cell Research & Therapy, 2025)
Cancer is a predominant cause of mortality globally, with both incidence and mortality rates consistently rising. The integrative nature of cancer, characterised by the coexistence of malignant and normal cells, diminishes the efficacy of single-modality therapies for both early-stage and late-stage tumours. Consequently, multimodal interventions, including surgery, radiation, chemotherapy, and immunotherapy, are necessary. Patient heterogeneity and cancer resistance complicate treatment outcomes, requiring personalised therapeutic approaches. Cancer cells operate as astute entities, collaborating with the human body to circumvent treatment, thus necessitating correspondingly intricate therapeutic approaches. Existing medicines are insufficient, rendering cancer a continual struggle for medical professionals and researchers. The progression of nanotechnology has led to the emergence of theranostics, which combines diagnosis and therapy into a unified approach. Nanotheranostic drugs, influenced by external stimuli such as light, magnetic fields, and ultrasound, signify a novel advancement in anti-cancer treatments. Although numerous stimuli-responsive theranostic nanomaterials have demonstrated proof-of-concept, none have progressed to clinical trials. This chapter examines diverse theranostic nanomaterials, emphasising inorganic agents utilised without chemical alterations. It evaluates the efficacy of theranostic agents licensed for preclinical and clinical trials. Chemotheranostics, radiotheranostics, immunotheranostics, and phototheranostics present considerable potential owing to their extensive surface area, customisable attributes, and biocompatibility. Notwithstanding significant progress, difficulties, including particle size, charge, medication stability, and surface changes, remain. Interdisciplinary collaboration among biological, pharmaceutical, materials science, and nanotechnology sectors is crucial for enhancing clinical translation. Tumor-specific theranostic biomaterials offer a targeted methodology, minimising toxicity and improving therapeutic efficacy while accounting for individual patient chracteristics.
Keywords: drug carcinoids